Vocabulary Enrichment through Picture Word Inductive Model (PWIM): An Experimental Study - Marpaung, Marlin Steffi (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2023)
Vocabulary is one of the important aspects in learning English. This study sought the answer of the following question: 1). Is there a significant difference on the students who are taught using Picture Word Inductive Model (PWIM) to improve vocabulary knowledge and students who were taught using conventional method? The sample in this research are 8th grade students of SMPN 3 Parongpong, Bandung Barat in academic year 2019/2020. The students were divided into two groups, one class was taught using Picture Word Inductive Model (PWIM) and the other one was taught using conventional method. This is quantitative research with an experimental design. The instrument used for this study was vocabulary test, which contained 35 questions. The result of the study showed that the pre-test for the experimental group was 51.73 and the conventional group was 51.63 while the post-test results for the experimental group was 78.63 and the conventional group was 60.83. In summary, it can be concluded that there is a significant different between students who were taught using Picture Word Inductive Model (PWIM) and the students who were taught using conventional method in improving students’ vocabulary knowledge. For further researcher, this study can be a reference for researchers to do another study with different level of students.